Th17/Treg imbalance mediates hepatic intolerance to exogenous lipopolysaccharide and exacerbates liver injury in triptolide induced excessive immune response. (15th September 2022) - Zhang, Haoran; Yuan, Ziqiao; Zhu, Ying; Yuan, Zihang; Wang, Jie; Nong, Cheng; Zhou, Shaoyun; Tang, Qianhui; Zhang, Luyong; Jiang, Zhenzhou; Yu, Qinwei
Abstract: Ethnopharmacological relevance: Triptolide (TP) is a major active ingredient and toxic component of Tripterygium wilfordii Hook F (TWHF), which exhibits multiple activities and remarkable hepatotoxicity, the latter of which limits its clinical application due to the risk of liver injury. Previous research has revealed the hepatotoxicity of TP resulting in liver hypersensitivity upon lipopolysaccharide (LPS) stimulation. However, existing research has not elucidated the potential immune mechanism such as Th17/Treg imbalance in TP-induced hepatic excessive immune response to exogenous LPS. Aim of the study: To investigate the role of Th17/Treg imbalance in TP-induced hepatic excessive immune response to exogenous LPS. Materials and methods: Mice were administered with TP, LPS, neutralization antibody and small molecule inhibitor respectively. Serum transaminase level was measured to determine the severity of liver injury. Frequencies of liver Th17 and Treg cells were analyzed by flow cytometry. Serum cytokine levels were performed by ELSIA, and mRNA levels of liver cytokine were performed by qPCR. The status of neutrophil infiltration was performed by myeloperoxidase (MPO) IHC measurement. Morphological observation of liver was performed by hematoxylin and eosin (H&E) staining. Results: Mice given a single intragastric dose of TP (500 μg/kg) developed lethal fulminant hepatitis following intraperitoneal injection of LPS (0.1 mg/kg), characterized by low survival rate, severe liver injury, high levels of inflammation and neutrophil infiltration. Hepatic Th17/Treg imbalance emerged together with liver injury in these mice. Neutralization of IL-17A attenuated the liver injury and ameliorated the neutrophil infiltration. The TP-induced alteration of hepatic Th17/Treg balance was closely related to the outcome of immune-mediated acute liver injury triggered by LPS. Pretreatment with the STAT3 inhibitor AG490 effectively restored Th17/Treg balance, significantly reducing the production of IL-17A and finally attenuating the degree of liver injury. Conclusion: Hepatic Th17/Treg imbalance not only exacerbates TP- and LPS-induced liver injury, but also serves as an indispensable part in the mechanisms of TP-induced hepatic intolerance to exogenous endotoxin. Graphical abstract: Image 1 Highlights: Th17/Treg imbalance emerged in the TP- and LPS-induced lethal hepatitis of mice. Th17/Treg imbalance exacerbated liver injury via IL-17A recruited neutrophils. TP induced Th17/Treg imbalance may be the mechanism of hepatic intolerance to LPS. Restored Th17/Treg balance attenuated TP- and LPS-induced fulminant hepatitis.